Social Maturity as a Factor in the Professional Self-Determination of an Adolescent Person - Huliaieva, Olena; Poltavska, Kateryna (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2024)
The article presents the results of an empirical study focused on the relationship between social maturity and professional self-determination in early adolescents. Theoretical criteria of social maturity—reflection, autonomy, and environmental management—are discussed as crucial aspects of personal development. The activity of a mature personality manifests in active creativity through processes of cognition, activity, and communication. Personal reflection involves self-awareness, self-discovery abilities, and self-directedness in interpersonal relations. Autonomy refers to the capability to resist majority opinions and to make conscious and independent decisions. The total sample of respondents aged 17-18 years was divided into two groups. The first group consisted of 32 graduates of the 11th grade; the second group consisted of 30 first-year university students. The results of the empirical study showed that graduates of the 11th grade who are in a crisis of professional development tend to rely on the opinion of society and build their lives according to the accepted standards. Those who have determined their professional direction demonstrate interest to self-knowledge but are characterised by passive social behaviour. First-year students, facing a crisis of choice, try to maintain their autonomy and uniqueness. Students with an established professional position try to be useful to society while remaining true to their values. A statistically significant difference was found in the level of development of reflexivity in adolescents. It was found that students are characterised by a higher level of self-acceptance, a higher level of self-esteem, etc. It has been established that reflexivity is an important quality that influences successful professional self-determination.